When It Doesn't Fit: Congenital Anomalies of the Choledochus - Helena Reusens; Mark Davenport (Georg Thieme Verlag KG, 2020)
Introduction Congenital choledochal malformations (CCMs) are characterized by intra- and/or extrahepatic bile duct dilatation. Five basic types (1-5) are recognized in Todani's classification and its modifications, of which types 1 and 4 typically have an associated anomalous pancreatobiliary junction and common channel (CC). We describe two cases with previously undescribed features. Case Report 1 Antenatal detection of a cyst at porta hepatis was made in an otherwise normal girl of Iranian parentage. She was confirmed to be a CCM (20 mm diameter), postnatally, with no evidence of obstruction. Surgical exploration was performed at 12 weeks. She had an isolated cystic dilatation of the right-hepatic duct only. The left-hepatic duct and common bile duct (CBD) were normal without a CC. Histology of the resected specimen showed stratified squamous epithelium. Case Report 2 A preterm (31 weeks of gestation) boy of Nigerian parentage was presented. His mother was HIV + ve and he was treated with nucleoside reverse transcriptase inhibitors following birth. He had persistent cholestatic jaundice and a dilated (10 mm) bile duct from birth. Although the jaundice resolved, the dilatation persisted and increased, coming to surgery aged 2.5 years. This showed cystic dilatation confined to the common hepatic duct, and otherwise normal distal common bile duct and no CC. Result Both underwent resection with the Roux-en-Y hepaticojejunostomy reconstruction to the transected right-hepatic duct alone in case 1, leaving the preserved left duct and CBD in continuity, and to the transected common hepatic duct in case 2. Conclusions Neither choledochal anomaly fitted into the usual choledochal classification and case 1 appears unique in the literature.